433 DELTA CHANGE IN SERUM CREATININE AS A PREDICTOR OF MORTALITY IN PATIENTS ON CONTINUOUS RENAL REPLACEMENT THERAPY. (1st January 2005) - Brar, H.; LeBrun, C.
Abstract : Though there have been many advances in the treatment of acute renal failure over the past four decades, the mortality of a critically ill patient who develops acute renal failure remains essentially unchanged. The development of continuous renal replacement therapy (CRRT) has allowed even the very critically ill patient to be placed on a form of dialysis. Unfortunately, published data to date have still not shown a significant survival benefit with CRRT therapy, and only limited studies have shown improved survival with increased amount of dialysis (as per clearance supplied to these patients). We prospectively collected data on CRRT patients at our institution in an attempt to correlate patient and dialysis characteristics with patient survival. Data are collected on 92 patients over an eighteen-month period who were treated with CRRT. Approximately 48% of patients survived thirty days post initiation of CRRT. We examined many patient and dialysis characteristics in an attempt to predict patient survival with CRRT. These included patient age, Apache II score initiation, blood pressure at initiation, and weight gained at the time of initiation of CRRT. None of these unfortunately correlated with patient survival. What did correlate in a statistically significant manner was change in creatinine from day of initiation to day of termination of CRRT. The average creatinine change in the patient surviving at thirty days was a decrease in creatinine by 2.64, while those who did not survive had an average decrease in serum creatinine of 1.77. This significant decrease in creatinine in survivors could be a reflection of improved dialysis clearance and/or improvement in residual renal function. We further analyzed the data looking at the subset of patients who survived but did not recover significant renal function and showed that their change in creatinine remained significant from those who did not survive. The average creatinine change in this subset was 2.48, suggesting that likely a large component of this change in creatinine is dialysis supplied and not improvement in residual renal function. These data support the idea of a beneficial effect of increased dialysis clearances in this patient population and may supply another clearance target for CRRT.